The effects of the technology application “Socrative” on student engagement in a baccalaureate nursing program - Amoia-Watters, Laraine (Teaching and learning in nursing, 2023)
•What is currently known about this topicThe use of technology in the classroom increases student engagement.•What the paper adds to the existing knowledgeTechnology in nursing class increase student engagement and perceptions of learning.•How the information can be applied to practiceEngagement in nursing classes aid in retention of information for future practice. The purpose of this study was to evaluate the effectiveness of incorporating technology into a sophomore level nursing class in a private university and to explore students’ perceptions on the use of technology in the classroom. A within-subjects study utilizing a quantitative design was utilized for the total study sample (n = 96). Data were collected from post-tests given to classes after traditional lectures as well as from post-tests given in lectures with the intervention of technology to gauge engagement to the presented material. Test results were compared to determine if there were statistically significant changes between these scores. The results of the post-tests were inconclusive as to the effectiveness of technology and student engagement. However, a survey was distributed to all students at the end of the study to gather total study sample information on student perceptions with the use of technology. The survey results were positive and indicated that students felt engaged in class material when using technology. The study directly addressed the following questions: • Does the use of a web-based application, such as Socrative, increase student engagement as evidenced by increased test scores? • Is there a positive perception of learning with the use of a web-based application, such as Socrative?